PERANAN SEKTOR PERTANIAN DALAM PENYERAPAN TENAGA KERJA DI KABUPATEN MINAHASA SELATAN (The Role of the Agricultural Sector in Employment in South Minahasa Regency) - Stenly Kumendong; Mex L. Sondakh; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aimed to determine the role of the agricultural sector in employment in South Minahasa Regency. This research was conducted for 3 months from October to December 2018. This study used secondary data obtained from the Central Statistics Agency of South Minahasa Regency. The results showed that the contribution of labor in the agricultural sector to the employment in South Minahasa Regency has decreased in the last two years, namely in 2017-2018. The employment contribution in the agricultural sector experienced an increase in labor absorption in 2015, but this increase was not able to cover the percentage of decline in the number of workers in the agricultural sector in 2017 and 2018.